2011
DOI: 10.1038/pj.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun composite nanofibers containing nanoparticles for the programmable release of dual drugs

Abstract: In this study, electrospun composite nanofibers containing nanoparticles for the programmable release of dual drugs were successfully fabricated through a one-step, single-nozzle electrospinning technique. Field-emission scanning electron microscopy and scanning electron microscopy were used to examine the morphology of the nanoparticles and electrospun nanofibers, respectively. The distribution of nanoparticles in the composite nanofibers was evaluated by fluorescence microscopy and laser scanning confocal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…They were linearly packed and aligned along the axes of the fibers, which is related to the viscosity gradient of the suspension during the electrospinning process. Similar results were reported by Wang and Norouzi et al for emulsion electrospinning [30,31]. containing chitosan nanoparticles was attributed only to chitosan degradation [34,[49][50][51].…”
Section: Page 13 Of 32supporting
confidence: 92%
See 1 more Smart Citation
“…They were linearly packed and aligned along the axes of the fibers, which is related to the viscosity gradient of the suspension during the electrospinning process. Similar results were reported by Wang and Norouzi et al for emulsion electrospinning [30,31]. containing chitosan nanoparticles was attributed only to chitosan degradation [34,[49][50][51].…”
Section: Page 13 Of 32supporting
confidence: 92%
“…In the present work, a system of core-shell structured nanofibers containing BSA-loaded nanoparticles was developed by suspension electrospinning to construct a bioactive scaffold with better protein structural preservation compared to common emulsion electrospinning techniques [31][32][33]. M a n u s c r i p t 5 Chitosan-based nanoparticles were applied as protein carriers since the encapsulated proteins in those nanoparticles have already been shown to be protected from the toxic solvent using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and circular dichroism (CD) spectroscopy [1,10,31,34].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the fine morphology of the electrospun fibers can be successfully created by the proper modulation of the solution properties; similar results have also been reported by other researchers. 9,17,[19][20][21][22][23][24][25] The Fourier-transform infrared spectra of the electrospun CA fibers showed a strong ester carbonyl stretching vibration at 1750 cm À1 , 26 whereas those of PEO fibers exhibited strong peaks at 2900 cm À1 that were attributed to the molecular stretching of methylene groups (CH 2 ). 9 The Fourier-transform infrared spectra of the CA-PEO fibers exhibited both of these characteristic peaks, as shown in Figure 4.…”
Section: Effects Of Peo and Zno Nps On Ca Nanocomposite Film C Pittarmentioning
confidence: 99%
“…Core-sheath fibers combine the two most desirable properties of tissue engineering, i.e., sustained and targeted delivery of biomolecules with template of tissue regeneration (scaffold). Recently, existing knowledge of particulate technology for drug delivery applications has been integrated with core-sheath nanofibers [66,95,96]. The encapsulation of biomolecules-loaded nanoparticles and liposomes into core-sheath fibrous scaffolds allow for the programmable delivery of multiple drugs together.…”
Section: Discussionmentioning
confidence: 99%
“…The controlled surface property and distinct release profile of a core-sheath nanofibrous device can be useful for therapeutic tissue engineering. In following years several other studies have reported multiple drug delivery systems including chitosan nanoparticles/ PCL with Rhodamine-B/naproxane model drugs in core-sheath nanofibers [94][95][96]. The implementation of core-sheath electrospun fibers for single and multiple drug deliveries demonstrated the potential of this technology.…”
Section: Drug Deliverymentioning
confidence: 99%